Electricity for development: Mini-grid solution for rural electrification in South Africa. (15th February 2016) - Azimoh, Chukwuma Leonard; Klintenberg, Patrik; Wallin, Fredrik; Karlsson, Björn; Mbohwa, Charles
Highlights: The use of hybrid mini-grid electricity for rural development is investigated. Solar home system electricity has limited development impact on rural households in South Africa. Mini-grid-solution for rural electrification is able to sustain and initiate small scale businesses. Hydro based hybrid mini-grids have more potential to meet the energy needs of rural households. Abstract: The objective of most rural electrification programs in the developing world is to bring about socio-economic development to households. Governments have put in place a number of measures to achieve this goal. Previous studies on rural electrification programs in developing countries show that solar home systems and mini-grid systems are the dominant technologies. Assessments of a pilot hybrid mini-grid project at Lucingweni village have concluded that mini-grid projects are not feasible due to high electricity production costs. As a result efforts toward rural electrification have been focused on the solar home system. Nevertheless, previous studies of the South African solar home system program have shown that the development objectives of the program are yet to be met more than a decade after commissioning. Therefore, this study investigates the viability of a hybrid mini-grid as a solution for rural development in South Africa. Investigations were based on Lucingweni and Thlatlaganya, two rural Villages where the mini-grid and solar home system have been introduced. The mini-grid systems were designed taking into consideration available natural resources and existing load profiles. The results show that a village of 300 households needs about 2.4 kW h/household/day of electricity to initiate and sustain income generating activities and that the solar home system is not capable of supporting this level of demand. We also show that in locations with hydro resources, a hybrid mini-grid system has the most potential for meeting the energy needs of the households in a cost effective manner. The assessment shows that with adequate planning and optimization of available resources, the cost of electricity production can be reduced.